Body weight perception versus body weight status: how good is the agreement? - Jamani, Nurjasmine Aida; Said, Abdul Hadi; Abd. Aziz, Karimah Hanim; Abd Rahman, Mohd Aizuddin (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Body weight perception is an important underlying psychological factor associated with body weight. Overemphasis on thinness among adolescents can lead to unhealthy dieting practices and eating disorders, whereas underestimation of body weight may increase risk of the development of overweight and obesity. This study measured the agreement between body weight perception and body weight status (BMI) among late adolescents in Kuantan.